2020
DOI: 10.1186/s12917-020-02636-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with different concentration of molasses on growth performance, blood metabolites and rumen fermentation indices of Nubian goats

Abstract: Background Molasses is a potential energy supplement; extensively used to improve growth performance, milk and meat characteristics in goats at relatively low concentrations of 5–40% of the diet. Few data are available concerning feeding molasses to goat kids; therefore, the current study aimed to investigate the effects of dietary supplementation with higher concentrations of molasses on growth performance, blood metabolites and rumen fermentation indices. Twenty male Nubian goat kids (4–6 months old; 9–10 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(63 reference statements)
3
1
0
Order By: Relevance
“…The results of our study agreed with what Alshefea and Hassan (2021) obtained from a highly significant increase (P<0.01) in the daily weight gain and final weight, our results also agreed with what was found by Al-Mamouri (2022) that there is a highly significant (P<0.01) in the daily and total weight gain in favor of urea treatment (7.17%) compared with the untreated when replacing treated and untreated yellow corn impurities instead of wheat bran in feeding of Awassi lambs, it also agreed with what was found by Osman et al (2020) that there was a highly significant increase (P > 0.0001) in final weight and daily gain in a group fed with addition of 40% molasses compared to other groups when feeding young Nubian goats due to increased palatability of molasses, and also agreed with the results of Abera et al (2016), while our results did not agree with what Saro et al (2019) found, there are no significant differences in the daily weight gain and final weight when replacing soybean with urea in fattening Assaf lambs.…”
Section: Resultssupporting
confidence: 93%
“…The results of our study agreed with what Alshefea and Hassan (2021) obtained from a highly significant increase (P<0.01) in the daily weight gain and final weight, our results also agreed with what was found by Al-Mamouri (2022) that there is a highly significant (P<0.01) in the daily and total weight gain in favor of urea treatment (7.17%) compared with the untreated when replacing treated and untreated yellow corn impurities instead of wheat bran in feeding of Awassi lambs, it also agreed with what was found by Osman et al (2020) that there was a highly significant increase (P > 0.0001) in final weight and daily gain in a group fed with addition of 40% molasses compared to other groups when feeding young Nubian goats due to increased palatability of molasses, and also agreed with the results of Abera et al (2016), while our results did not agree with what Saro et al (2019) found, there are no significant differences in the daily weight gain and final weight when replacing soybean with urea in fattening Assaf lambs.…”
Section: Resultssupporting
confidence: 93%
“…The values of results showed no significant effects on plasma AST and ALT concentrations with different treatments , this indicates that goats were in normal health without any adverse effects of (BW) supplementation on liver function ,this agree with Osman et al (2020) who found that values of AST and ALT in normal range when increasing molasses levels in ration. urea and creatinine concentrations were in the normal range, urea and creatinine not affected with experimental rations compared to control Supplemented groups had significantly increase in concentrations of cholesterol and triglycerides.…”
Section: Blood Parameterssupporting
confidence: 85%
“…The high body weight gains of goats fed to Mulato II or ML could be due to high crude protein and metabolisable energy content in the diets. Similar observations were reported that once the grass is mixed with legumes/shrubs increase quality of diets and palatability thus, increases goats' production (Alvarez et al, 2018;Osman et al, 2020). This is due to the quality of dry matter intake which characterises the increase of body weight gain Gusha et al (2015).…”
supporting
confidence: 67%